NEGARA HUKUM DALAM PERSPEKTIF FILSAFAT HUKUM - Zahra Putri (PT. Habe Cendekia Utama, 2025)
The rule of law is a fundamental concept in the modern government system that places law as the basis for the legitimacy of power and the protection of human rights. From the perspective of the philosophy of law, the rule of law includes normative, philosophical, and historical dimensions that are interrelated. This article discusses the concept of the rule of law through a philosophy of law approach, including classical thoughts such as Plato and Aristotle, to modern developments in the views of Hans Kelsen and Lon Fuller. The analysis is carried out to describe the main principles such as the supremacy of law, separation of powers, and respect for human rights within the framework of the rule of law. This paper also explores the relevance of the concept of the rule of law in facing contemporary challenges, such as globalization and technological developments. Through this approach, it is hoped that it can provide a deeper understanding of the essence of the rule of law as the main pillar in social and state life.